1971
DOI: 10.1002/bip.360100303
|View full text |Cite
|
Sign up to set email alerts
|

DNA–copper(II) complex and the DNA conformation

Abstract: Jlilirobioloyie und experimentelle Therapie der Deutschen Akademie der Synopsis Spectrophotometric, sedimentation, infrared, optical rotatory dispersion (Oltl)), and circxilar dichroisni (CI)) methods have beeti used to demonstrate the structural changes in DNA induced by the iiiteractioii of copper(I1) with bases and to elucidate the complex binding sites. As showii by the electrolyt,e-induced reversion (addit ion of salts) of temperat~ire-deriat~ired cwpper I ) S A the effectiveness of re-formation of the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 48 publications
4
68
0
2
Order By: Relevance
“…The CD spectra of the DNA . Cu2+ complexes [29,31] are perhaps those which come closest to that of the DNA . tran~-Pt(NH3)~C12 complexes.…”
Section: S@ctra Of D N a Pt Complcuc~mentioning
confidence: 99%
“…The CD spectra of the DNA . Cu2+ complexes [29,31] are perhaps those which come closest to that of the DNA . tran~-Pt(NH3)~C12 complexes.…”
Section: S@ctra Of D N a Pt Complcuc~mentioning
confidence: 99%
“…Further, the concentration of antioxidant required for such a cytotoxic action should be lower as the concentration of copper increases. Indeed, it has been shown that ascorbic acid is cytotoxic to leukemic cells (3-to 4-fold higher copper levels [22] ) at a much lower concentration than normal lymphocytes [14] . This would also account for the observation that ascorbic acid selectively targets the cancer cells while normal cells are spared from such cytotoxic effects [29,38] .…”
Section: Resultsmentioning
confidence: 99%
“…1 ) [6] . Copper ions are known to interact with both DNA phosphates and the bases through coordination binding [22] . These findings demonstrate that the ascorbate-Cu(II) system for DNA breakage is physiologically feasible and could be of biological significance.…”
Section: Oxidative Dna Cleavage By Ascorbate In Vitro and In Human Lymentioning
confidence: 99%
“…5 Specifically, there is a substantial effect of the Cu cation on T m and on the conformation transformation (B-DNA→Z-DNA) of DNA. 5,11,12 Interaction of Cu cation with DNA as a part of [metal·DNA] complex have also been studied extensively using IR, 13,14 X-ray, 12,15 along with other techniques. 16,17 Cu cation prefers to interact with the backbone phosphate negative groups through nonspecific electrostatic attraction, which stabilizes the DNA helix structure.…”
Section: Introductionmentioning
confidence: 99%